A Case of CCDC6-RET Fusion Mutation in Adult Acute Lymphoblastic Leukemia (ALL), a Known Activating Mutation Reported in ALL - Mejia Saldarriaga, Mateo; Steinberg, Amir; Severson, Eric A.; Binder, Adam (Frontiers in Oncology, 2019)
We report the case of a patient with B-Cell Acute Lymphoblastic Leukemia (ALL) who was found to harbor a gene fusion involving the CCDC6 and RET genes. Although the RET mutations have been identified before in other malignancies, and it is thought to represent a driver mutation in these neoplasms, it has yet to be described in ALL. The identification of known fusion genes conferring activating tyrosine kinase activity in neoplasms can suggest potential therapeutic role of tyrosine kinase inhibitors (TKI), an approach that has been exploited in several other fusion genes.